Design and Analysis of a Multifingered Robot Hand - Pramod Kumar Parida; Bibhuti Bhusan Biswal (IAES International Journal of Robotics and Automation (IJRA), 2012)
With the advent of new control techniques and development of microactuators, manipulator designers have gained inpetus todevelop manipulators and the related devicesthat is more flexible, responsive, smart and anthropomorphic.Taking cue from the work of a number of researchersover a couple of decades, the present work is a systematic attempt to develop a five fingered anthropomorphic robotic hand with 25 DoFs. The hand closely follows the anatomy of a typical human hand. The paper presents the structure of the proposed hand and its model for kinematic analysis. The kinematic analysis has been carried out using conventional method using MATLab software. The result obtained through the analysis confirmed that the robot hand conforms to the objective.DOI: http://dx.doi.org/10.11591/ijra.v1i2.360